ANALISIS FAKTOR TINGKAT PRODUKSI TERHADAP PENDAPATAN USAHATANI CABAI MERAH (STUDI KASUS DI DESA BATURITI, KECAMATAN BATURITI KABUPETAN TABANAN) - LESTARI, PUTU FAJAR KARTIKA (Universitas Mahasaraswati K. Mataram, 2024)
Red chilies are a source of income for some farmers in Baturiti Village, Baturiti District, Tabanan Regency. This research aims to determine income and factors that influence red chili farming income. The research was conducted in Baturiti Village, Baturiti District, Tabanan Regency. The data taken includes primary and secondary data. Primary data was taken through interviews using a structured questionnaire with 60 farmers as respondents. Multiple linear regression models were used to analyze the data. The results of the analysis show, (1) The average red chili farming income is IDR 78,661,752.00 per hectare; and (2) seeds, KCl fertilizer, NPK fertilizer, ZA fertilizer, chicken manure, and red chili prices have a positive and real effect on income, while pesticides have a significant and negative effect on income.